Relationship Between Epicardial Adipose Tissue, Inflammation and Volume Markers in Hemodialysis and Transplant Patients. Issue 1 (February 2015) - Çolak, Hülya; Kilicarslan, Baris; Tekce, Hikmet; Tanrisev, Mehmet; Tugmen, Cem; Aktas, Gulali; Kursat, Seyhun
Abstract Cardiovascular (CV) diseases are still the most important cause of morbidity and mortality in both patients receiving hemodialysis (HD) treatment and individuals with renal transplantation (Rtx). Measurement of epicardial adipose tissue (EAT) thickness is an easily applied, cheap, and useful recent method predicting increased CV risk. We aimed to compare EAT changes in HD and Rtx patients and the association between EAT and inflammatory and CV volume markers in both groups. A total of 124 patients: 45 Rtx, 43 HD patients and 36 healthy controls were enrolled in the study. Laboratory parameters and inflammatory markers (interleukin‐6 [IL‐6] and high sensitive C‐reactive protein [Hs‐CRP]) were evaluated from venous blood samples after an overnight fast. EAT thickness was measured with transthoracic echocardiography. The levels of Hs‐CRP, IL‐6, systolic and diastolic blood pressures, left atrial (LA) diameter, left atrial index (LAI), left ventricular mass (LVM) and LVM index (LVMI) were significantly higher in the HD patients than in the other groups. EAT was positively correlated with age, body mass index (BMI), time on dialysis, serum creatinine, total cholesterol, Low density lipoprotein‐cholesterol, and LVM in Rtx group and positively correlated with age, BMI, duration of dialysis, Hs‐CRP, IL‐6, LAI and LVMI and inversely correlated with inferior vena cava collapse index (IVC‐CI) in HD group. EAT thickness of RTx patients (whose previous HD duration was similar to those in HD group) are similar to the healthy population and significantly thinner than patients on HD.